Intersecting identities and interculturality: discourse and practice - Machart, Regis (Cambridge Scholars Publishing, 2013)
Most scholars now refute the monolithic, static definition of identity and adopt a fluid approach to the concept which takes into consideration overlapping, or rather intersecting the different facets of identity. The contact of many and varied aspects of identity finds its full development in interpersonal communication when two or more individuals identify through their discourse. In this volume the authors are interested in identity in intercultural contexts. Interculturality is understood as interculturality without culture (Dervin 2010), not only focusing on cultural differences but expanding to gender, occupation, social class, etc. The contributors in this book consider that the different components/aspects of one's identity are not necessarily opposed to each other, that someone's identity is not pre-determined and that different voices can be heard from within a given group. With contributions from Finland, Japan, Malaysia, Romania, the United Kingdom and the United States of America from the fields of linguistics, sociolinguistics, discourse analysis, linguistic anthropology, cultural anthropology, literature and education, the key concepts associated with identity and interculturality are revisited, and empirical research provides an insight on identification processes. This volume will appeal to scholars interested in the questions of identity and intercultural relations, as well as to students, particularly from the fields of anthropology, education, language and communication studies who try to better understand the discursive interactions between two people. It will also interest individuals from all walks of life who are keen on knowing more about personal diversities.